Frequency of Adequate Knowledge and Attitude of Females of Reproductive age towards IUCD as Emergency Contraception after an Unprotected Intercourse - Nadia Leghari, Abida Rehman, Sadia Nazir, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The objective of this study is to determine the frequency of adequate knowledge and attitude of females of reproductive age about IUCD as emergency contraception after an unprotected intercourse. Study Design: Cross sectional study Settings: Obstetrics & Gynecology, D. G. Khan Hospital D. G Khan Study duration: 6 months (April 2021 to October 2021) Procedure for data Collection: A total of 305 females who met the selection criteria were enrolled in the study through the OPD of the Department of Obstetrics and Gynecology at D. G. Khan Hospital D. G Khan. All females were asked for their knowledge and attitude towards IUCD as emergency contraception by researcher herself. A predesigned proforma was used to assess their knowledge and attitude of females towards IUCD as emergency contraception. Knowledge and attitude was labeled. Results: In this study 274(89.94%) women’s knowledge was adequate regarding IUCD as EC and 156(51.15%) women showed positive attitude for it. Knowledge adequacy for IUCD was higher in women in the age group 30-40 years as compared to lower age group. I.e. 20-30 years. I.e. 20-30 years: 88.9% vs. 30-40 years: 91.2% (p-value=0.511). However no statistically significant difference was observed for knowledge adequacy in both age groups women. The same trend was seen for positive attitude of women for IUCD in terms of age group. I.e. 20-30 years. I.e. 20-30 years: 48.9% vs. 30-40 years: 54.4% (p-value=0.344). Conclusion: Results of this study showed high level of knowledge and positive attitude of women for IUCD use as EC. EC has the potential to provide women with an important fertility control option. Healthcare providers can play an important role in educating their patients about EC. Keywords: EC, IUCD, Knowledge, Pregnaancy.